Fortalecimiento de la diversidad arbórea melífera: plan de reforestación para la conservación de abejas meliponas en fincas de Santa Rita-Chone - Navarrete Parodi, Erika Karina (2025)
The objective of the study was to strengthen honey bee tree diversity through a reforestation plan on three farms in Santa Rita parish, Chone canton, Ecuador, to conserve honey bees and promote environmental sustainability. An initial diagnosis of tree diversity was made through forest inventories, followed by the design and implementation of a strategic plan that integrated native species of the area. Methodologies included direct observation, structured interviews and bibliographic analysis, complemented by community training on reforestation and sustainable practices. A high predominance of species from the Rutaceae family (Citrus reticulata, C. sinensis and C. paradisi) was identified, but the landowners' knowledge of their conservation was limited. The plan achieved an 85% survival rate of 150 seedlings (algarrobo (Prosopis pallida), guaba (Chorisia insignis), la guanábana (Annona muricata), el pechiche (Platymiscium pinnatum), el chisparo (Enterolobium cyclocarpum), la fruta de pan (Artocarpus altilis), el guayacán blanco (Tabebuia rosea), guayacan amarillo (Tabebuia chrysantha), el pachaco (Guaiacum sanctum) y el guasmo (Cochlospermum vitifolium).) in the first eight weeks, demonstrating their adaptation to the environment and community commitment. The training significantly increased local knowledge, generating positive changes in environmental management. In conclusion, the project strengthened the biodiversity and ecological functionality of the honey ecosystem, highlighting the role of native species and environmental education as fundamental pillars for conservation and sustainability.